Zerumbone enhances TRAIL-induced apoptosis through the induction of death receptors in human colon cancer cells: Evidence for an essential role of reactive oxygen species - Supachai Yodkeeree (2018)
Identification of the active component and mechanisms of action of traditional medicines is highly desirable. We investigated whether zerumbone, a sesquiterpene from tropical ginger, can enhance the anticancer effects of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL). We found that zerumbone potentiated TRAIL-induced apoptosis in human HCT116 colon cancer cells and that this correlated with the up-regulation of TRAIL death receptor (DR) 4 and DR5. Induction of DRs occurred at the transcriptional level, and this induction was not cell-type specific, as its expression was also up-regulated in prostate, kidney, breast, and pancreatic cancer cell lines. Deletion of DR5 or DR4 by small interfering RNA significantly reduced the apoptosis induced by TRAIL and zerumbone. In addition to up-regulating DRs, zerumbone also significantly down-regulated the expression of cFLIP but not that of other antiapoptotic proteins. The induction of both DRs by zerumbone was abolished by glutathione and N-acetylcysteine (NAC), and this correlated with decreased TRAIL-induced apoptosis, suggesting a critical role of reactive oxygen species. Inhibition of extracellular signal-regulated kinase 1/2 and p38 mitogen-activated protein kinase but not of Jun NH2-terminal kinase abolished the effect of zerumbone on DRinduction. Zerumbone also induced the p53 tumor suppressor gene but was found to be optional for DRinduction or for enhancement of TRAIL-induced apoptosis. Both bax and p21, however, were required for zerumbone to stimulate TRAIL-induced apoptosis. Overall, our results show that zerumbone can potentiate TRAIL-induced apoptosis through the reactive oxygen species-mediated activation of extracellular signal-regulated kinase 1/2 and p38 mitogenactivated protein kinase leading to DR4 and DR5 induction and resulting in enhancement of the anticancer effects of TRAIL. ©2009 American Association for Cancer Research.